Desenvolvimento de um microscópio confocal de varredura laser para caracterização topográfica de superfícies - Oliveira, André Rezende de Figueiredo (2012)
The objective of this is study is to develop a laser scanning confocal microscope, achieving submicron resolution in order to characterize surface topography. The laser scanned images are drawn point-by-point using control software. Comparing with other techniques of topographical characterization of surfaces: Laser Interferometer and Atomic Force Microscopy, the prototype showed a satisfactory performance. Confocal microscopy makes use of an optical technique that enhances contrast and builds three dimensional images by means of a pinhole. For the construction of a confocal image, a laser beam moves point-by-point and line-by-line on the sample surface. The device developed proved to be an appropriate a tool with adequate resolution to assess surfaces. The results are consistent with the best resolutions available, and the technique has potenctial to be employed in several research projects.